The Impact of Corporate Financial Disclosure Quality on Banks’ Loan Risk Assessment: A Case Study of Uzbekistan - Akhmedov, Behruz (European Scientific Journal, ESJ, 2025)
Corporate financial disclosure quality plays a decisive role in banks’ loan risk assessment, particularly in emerging markets where reporting practices remain uneven. In Uzbekistan, the ongoing expansion of IFRS (International Financial Reporting Standards) and the shift toward risk-based banking supervision have increased the need for accurate, timely, and comparable borrower financial information. However, disclosure quality, especially among SMEs (Small and Medium-sized Enterprises), remains inconsistent, limiting banks’ ability to conduct cash-flow-based analysis and increasing reliance on collateral. This study examines how disclosure quality affects banks’ credit risk assessment in Uzbekistan using a conceptual mixed-method approach. Due to the scarcity of standardized borrower-level datasets and inconsistent audited reporting, econometric analysis is not feasible; instead, the study synthesizes existing empirical and regulatory evidence to identify key disclosure risk channels. Drawing on international research and Basel III requirements for data integrity, the paper shows that weak disclosures undermine reliable PD (Probability of Default) and LGD (Loss Given Default) estimation, distort risk-weighted asset calculations, and reduce the effectiveness of supervisory review and market discipline. The study concludes that improving financial reporting quality, advancing practical IFRS adoption for SMEs, and enhancing enforcement and digital data infrastructure are essential for strengthening risk assessment accuracy and reducing credit misclassification in Uzbekistan.